1945
DOI: 10.1017/s0022029900032350
|View full text |Cite
|
Sign up to set email alerts
|

325. A study of the balance of certain milk nutrients in the making of Cheddar, Cheshire and Stilton cheeses, and of their fate during the ripening of the cheeses

Abstract: 1. Cheshire, Cheddar and Stilton cheeses were made on one occasion from winter, and on another from summer, milk.2. The distribution of vitamin A and carotenoids, vitamin B1, riboflavin and vitamin C between milk, whey and curd was measured during cheese-making.3. The fate of these vitamins during ripening was determined.4. Some 80% of vitamin A and carotene, 15% of vitamin B1 and 25% of riboflavin originally present in milk were recovered in the green cheese and persisted throughout ripening.5. Vitamin C disa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
1
1

Year Published

1946
1946
1985
1985

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 26 publications
1
2
1
1
Order By: Relevance
“…The increase was more pronounced during the first 4 days of ripening. Though little is known about changes during accelerated ripening, the trend observed for riboflavin was similar to that reported earlier by Dearden et al (1945) who found no change in riboflavin during curing of cheese. The riboflavin content in 8 days accelerated cheese was found to be comparable to the level observed in the conventionally ripened cheese (Type B).…”
Section: Changes In Vitamin Content During Accelerated Ripeningsupporting
confidence: 88%
“…The increase was more pronounced during the first 4 days of ripening. Though little is known about changes during accelerated ripening, the trend observed for riboflavin was similar to that reported earlier by Dearden et al (1945) who found no change in riboflavin during curing of cheese. The riboflavin content in 8 days accelerated cheese was found to be comparable to the level observed in the conventionally ripened cheese (Type B).…”
Section: Changes In Vitamin Content During Accelerated Ripeningsupporting
confidence: 88%
“…The results of this experiment are given in Tables 2-4. The biological value of 52 now obtained for white bread was rather higher than the values of 45 and 48 previously obtained by us with the same bread (18), while the value of 76 obtained for the cheese was slightly higher than the value of 72 previously found in this laboratory (19) for a different sample of Cheddar cheese, and of 73 observed by Beadles, Quisenberry, Nakamura & Mitchell (20) for Swiss cheese, both at an 8 % level of protein. With the bread and cheese fed together, each supplying 50% of the protein, a marked supplementary effect was obvious as the biological value of the mixture, 75, was almost identical with that of the cheese alone.…”
Section: Resultscontrasting
confidence: 64%
“…When, however, the two proteins were fed on alternate days the resulting biological value of 67 was only slightly higher than the value of 64 which would be expected if there were no supplementary relationship. The values found now for the true digestibility of bread, 99, and of Cheddar cheese, 100, were higher than the values 93 and 98, respectively, previously found in this laboratory for these foods (18,19). The true digestibility of the mixture of proteins (diet 154) was 98 and of the diets fed alternately, 99.…”
Section: Resultsmentioning
confidence: 58%
“…have been used as the source of fat, the latter when it was inconvenient or impossible to obtain butter from the factories under consideration. It was thought safe to do this as the work of Dearden et al (1946) points to the complete conservation of vitamin A /g. of fat during the manufacture and maturing of cheese and the unpublished work of one of the authors (W.M.B.)…”
Section: ( B) the Determination Of Carotenementioning
confidence: 99%